EXPLORING THE ROLE OF ARTIFICIAL INTELLIGENCE (AI) IN SHAPING YOUTH'S WORLDVIEW IN EDUCATION (Ustozlar uchun, 2024)
This research paper delves into the evolving role of Artificial Intelligence (AI) in education and its profound impact on shaping the worldview of today's youth. AI technologies are increasingly integrated into educational settings, offering personalized learning experiences, intelligent tutoring systems, and data-driven insights. Through a comprehensive review of literature, analysis of case studies, and examination of AI-driven educational platforms, this paper explores how AI influences youth's perceptions of technology, learning approaches, and future career aspirations. Key topics include AI applications in education, benefits and challenges, ethical considerations, and implications for youth's technological worldview.